Calcific Metamorphosis: A Review - Siddiqui, Shoaib Haider; Mohamed, Ahmed Nabil (International Journal of Health Sciences, 2016)
Dental trauma to the permanent dentition can lead to clinical complications and its management may considerably challenge a practitioner. The incidence of pulp canal obliteration following dental trauma has been reported to be approximately 4 - 24%. Attempting to locate canals following calcific metamorphosis and negotiating it to full working length may lead to iatrogenic errors such as fractured instrument and perforation. This review article describes the possible etiology of Calcific Metamorphosis, its clinical and radiographic features as well as its management. Â 